Light-Dependent Activation of the GCN2 Kinase Under Cold and Salt Stress Is Mediated by the Photosynthetic Status of the Chloroplast - Lokdarshi, Ansul; Morgan, Philip W.; Franks, Michelle; Emert, Zoe; Emanuel, Catherine; von Arnim, Albrecht G. (Frontiers in Plant Science, 2020)
Regulation of cytosolic mRNA translation is a key node for rapid adaptation to environmental stress conditions. In yeast and animals, phosphorylation of the α-subunit of eukaryotic translation initiation factor eIF2 is the most thoroughly characterized event for regulating global translation under stress. In plants, the GCN2 kinase (General Control Nonderepressible-2) is the only known kinase for eIF2α. GCN2 is activated under a variety of stresses including reactive oxygen species (ROS). Here, we provide new evidence that the GCN2 kinase in Arabidopsis is also activated rapidly and in a light-dependent manner by cold and salt treatments. These treatments alone did not repress global mRNA ribosome loading in a major way. The activation of GCN2 was accompanied by a more oxidative environment and was attenuated by inhibitors of photosynthetic electron transport, suggesting that it is gated by the redox poise or the reactive oxygen status of the chloroplast. In keeping with these results, gcn2 mutant seedlings were more sensitive than wild type to both cold and salt in a root elongation assay. These data suggest that cold and salt stress may both affect the status of the cytosolic translation apparatus via the conserved GCN2-eIF2α module. The potential role of the GCN2 kinase pathway in the global repression of translation under abiotic stress is discussed.